HUBUNGAN ANTARA FREKUENSI MENGGOSOK GIGI DENGAN KEJADIAN CARIES DENTIS PADA SISWA KELAS II SD NEGERI SUMBER AGUNG II KLEGO - Ratna Indriati; Rahayu Setyaningsih; Tri Susilowati (Sekolah Tinggi Ilmu Kesehatan Panti Kosala, 2013)
Background. Incidence of dental caries in primary school children is stillrelatively high. This corresponds to a pattern of wrong eating habits, asupportive environment such bad habits like sweet snacks, less fibrous andeasily sticky. In addition the frequency of irregular brushing teeth also contributeto the occurrence of dental caries.The purpose this study was to determine the relationship between thefrequency of brushing teeth with dental caries incidence of grade 2 studentsSDN Sumberagung II Klego. The hypothesis taken by the researchers issuspected there is a relationship between the frequency of brushing teeth withdental caries incidence in Class 2 SDN Sumberagung II Klego. This study wasconducted in SDN II Suberagung Klego.Methods used is the correlation method with cross sectional approach, thenumber of samples of 50 people the sampling technique used is total samplingThe conclusion From the results of data processing, the chi squere obtained x2count equal to 9.314 and 3.841 on the table at the 0.05 significance level anddegrees of freedom equal to 1 so that the count is greater than x2 table whichmeans there is a relationship between the frequency of brushing teeth withdental caries incidence in 2nd grade students of SDN Sumberagung II Klego.This shows that with regular brushing can minimize the occurrence of dentalcariesKeywords : Dentis caries, Dental Care and Teeth Brushing